Peculiarity of metareflection in the novel “Foe” by J. M. Coetzee - Пшенична, Марія Сергіївна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
The specificity of metareflection in the novel “Foe” by South African writer J. M. Coetzee is examined in this article. The metareflection is a manifestation of self-reflectivity of the work of art which emerges in the novel in a form of metatext and intertext. Owing to the metareflection in the text the specified fictional reality arises, that expressly demonstrates literary hegemony, affectation and simulated nature of artistic work. Due to the metastructure the basic ideas of poststructuralism such as «archi-writing» and «the death of the author» is represented in the novel.